UPAYA MENINGKATKAN DISIPLIN KERJA KARYAWAN PT. SMART TALENTA MULTITAMA MELALUI FUNGSI PENGAWASAN - Lukman Effendhi; Ary Sutrischastini (Sekolah Tinggi Ilmu Ekonomi Widya Wiwaha, 2022)
The aims of this study are 1) to identify the causes of employee discipline at PT. Smart Talenta Multitama is not yet optimal and 2) determines efforts to improve the work discipline of employees of PT. Smart Talenta Multitama through the supervisory function. This research is a qualitative research. Data collection techniques were carried out using a questionnaire. The number of samples is 13 employees with purposive sampling method. Data analysis consists of three paths, namely data reduction, data presentation and drawing conclusions.The results showed that 1) the causes of work discipline at PT. Smart Talenta Multitama has not been maximized, namely low absenteeism, accuracy in entering and leaving work and adherence to regulations. This can be seen from the average value of the three indicators of 2.19 which is in the unfavorable category. 2) Efforts to increase supervision to improve the work discipline of employees of PT. Smart Talenta Multitama are: a) The frequency of supervision must be increased so that the employee work does not deviate from the established provisions;b) The supervision carried out should pay attention to attendance, the accuracy of entering and leaving work for employees, and compliance with regulations so that employee work discipline increases; and c) Leaders should reward disciplined employees and punish employees who do not follow the rules or are not disciplined.